Early management of adult sepsis and septic shock: Korean clinical practice guidelines - Chul Park; Nam Su Ku; Dae Won Park; Joo Hyun Park; Tae Sun Ha; Do Wan Kim; So Young Park; Youjin Chang; Kwang Wook Jo; Moon Seong Baek; Yijun Seo; Tae Gun Shin; et al. (Acute and Critical Care)
Background Despite recent advances and global improvements in sepsis recognition and supportive care, mortality rates remain high, and adherence to sepsis bundle components in Korea is low. To address this, the Korean Sepsis Alliance, affiliated with the Korean Society of Critical Care Medicine, developed the first sepsis treatment guidelines for Korea based on a comprehensive systematic review and meta-analysis. Methods A de novo method was used to develop the guidelines. Methodologies included determining key questions, conducting a literature search and selection, assessing the risk of bias, synthesizing evidence, and developing recommendations. The certainty of evidence and the strength of recommendations were determined using the Grading of Recommendations, Assessment, Development, and Evaluations approach. Draft recommendations underwent internal and external review processes and public hearings. The development of these guidelines was supported by a research grant from the Korean Disease Control and Prevention Agency. Results In these guidelines, we focused on early treatments for adult patients with sepsis and septic shock. Through the guideline development process, 12 key questions and their respective recommendations were formulated. These include lactate measurement, fluid therapies, target blood pressure, antibiotic administration, use of vasopressors and dobutamine, extracorporeal membrane oxygenation, and echocardiography. Conclusions These guidelines aim to support medical professionals in making appropriate decisions about treating adult sepsis and septic shock. We hope these guidelines will increase awareness of sepsis and reduce its mortality rate.